Correlation analysis between renal anatomical factors and residual stones after an ultrasound-guided PCNL - Zhu, Shusheng; Fan, Yanpeng; Hu, Xia; Shao, Mingming (Frontiers in Surgery, 2023)
Introduction To predict the factors of residual stones after percutaneous nephrolithotomy (PCNL) by analyzing the characteristics of the renal anatomical structure in intravenous urography, so as to make a reasonable operation plan, reduce the risk of residual stones in PCNL, and improve the stone-free rate (SFR). Methods A retrospective study was performed between January 2019 and September 2020 for patients treated with PCNL. According to the results of a kidney ureter bladder review after PCNL, 245 patients were divided into a residual stone group (71 patients, stone size >4 mm) and a stone-free group (174 patients, stone size ≤4 mm). An independent sample t-test was used to analyze the age, the length and width of channel calices, the angle between the channel calices and the involved calices, and the length and width of the involved calices. The gender, the channel types, the number of channels, the degree of hydronephrosis, and the number of involved calices were analyzed by using the chi-square test. A score of p < 0.05 was considered statistically significant. At the same time, logistic regression analysis was carried out to explore the independent influencing factors of the SFR after PCNL. Results A total of 71 patients developed residual stones after surgery. The overall residual rate was 29.0%. The width of the channel calices (p = 0.003), the angle between the channel calices and the involved calices (p = 0.007), the width of the involved calices (p < 0.001), the channel types (p = 0.008), and the number of involved calices (p < 0.001) were all significantly correlated with residual stones after PCNL. Logistic regression analysis showed that the width of the channel calices (p = 0.003), the angle between the channel calices and the involved calices (p = 0.012), the width of the involved calices (p < 0.001), the channel types (p = 0.008), and the number of involved calyces (p < 0.001) were all independent influencing factors of the SFR after PCNL. Conclusion A larger caliceal neck width and angle can reduce the risk of residual stones. The more calyces that are involved, the higher the risk of residual stones. There was no difference between F16 and F18, but F16 had a higher SFR than F24.